Protein phosphatase 2A mediates YAP activation in endothelial cells upon VEGF stimulation and matrix stiffness - Jiang, Xiao; Hu, Jiandong; Wu, Ziru; Cafarello, Sarah Trusso; Di Matteo, Mario; Shen, Ying; Dong, Xue; Adler, Heike; Mazzone, Massimiliano; Ruiz de Almodóvar, Carmen; Wang, Xiaohong (Frontiers in cell and developmental biology, 2021)
Angiogenesis is an essential process during development. Abnormal angiogenesis also contributes to many disease conditions such as tumor and retinal diseases. Previous studies have established the Hippo signaling pathway effector Yes-associated protein (YAP) as a crucial regulator of angiogenesis. In ECs, activated YAP promotes endothelial cell proliferation, migration and sprouting. YAP activity is regulated by vascular endothelial growth factor (VEGF) and mechanical cues such as extracellular matrix (ECM) stiffness. However, it is unclear how VEGF or ECM stiffness signal to YAP, especially how dephosphorylation of YAP occurs in response to VEGF stimulus or ECM stiffening. Here, we show that protein phosphatase 2A (PP2A) is required for this process. Blocking PP2A activity abolishes VEGF or ECM stiffening mediated YAP activation. Systemic administration of a PP2A inhibitor suppresses YAP activity in blood vessels in developmental and pathological angiogenesis mouse models. Consistently, PP2A inhibitor also inhibits sprouting angiogenesis. Mechanistically, PP2A directly interacts with YAP, and this interaction requires proper cytoskeleton dynamics. These findings identify PP2A as a crucial mediator of YAP activation in ECs and hence as an important regulator of angiogenesis.